Program development of best practices for students with traumatic brain injury - Guttormsen, Elin, author; Sample, Pat, advisor; Greene, David, committee member; Daunhauer, Lisa, committee member (Colorado State University. Libraries, 2014)
Rationale: Recent changes in Colorado legislation have led to implementation of new procedures in identification and classification of students with traumatic brain injury (TBI). The purpose of this study was to chronicle the subsequent process of training school personnel in Colorado to increase their capacity to implement the new school-based identification, assessment, and intervention processes for students with TBI. Methods: The study employed an interpretive case study design. Data collection measures included documentation review, field observations, and interviews with key informants. Results: Three thematic and chronological phases emerged from data analysis: (1) identifying the need for program change, (2) increasing awareness through preliminary staff trainings, and (3) creating expertise through secondary staff trainings. Discussion: Emergent themes present in program development included professional development, staff leadership, and interdisciplinary collaboration, and are supported by theoretical research. This program development in Colorado can serve as a procedural guide for other states attempting to implement new best practices for students with TBI.
Keywords: brain injury; children; Colorado; education; students; training